Developing spiritual intelligence: some new evidence - Fontaine, Rodrigue Ancelot Harvey (Centre for Research on Islamic Management and Business, 2018)
Although the nature of spiritual intelligence (and how to measure it) is becoming clearer (King, 2008), there is a lack of empirical evidence with regards to how to develop it. Since 2010, this author has focused on identifying processes to develop spiritual intelligence and some empirical evidence has already been presented elsewhere (Fontaine, 2011, Fontaine & Ahmad, 2013). Developing spiritual intelligence for Muslims is easy because spiritual intelligence is linked to reflecting on relevant Islamic knowledge. At the beginning of the semester, 103 students at the International Islamic University Malaysia were assessed on their level of spiritual intelligence using the instrument devised by King (2008). As part of their coursework, they had to listen to one Islamic talk a week on the Internet and keep a weekly diary of their reflections. They were free to choose the topic that interested them. Their task was to listen to the talk and write a weekly diary of their reflections. At the end of the semester, students’ level of spiritual intelligence was measured a second time. There was a significant improvement in the students’ level of spiritual intelligence, thus confirming the data presented in Fontaine and Ahmad (2013). This results suggests that developing spiritual intelligence can become a systematic and predictable process. Since then, this author has modified his framework and put more emphasis on tafsir of Qur’an as being the key success factor. The implications for leaders wishing to develop an organizational culture based on Islamic principles are discussed.